An investigation into the influence of longitudinal creepage on railway squeal noise due to lateral creepage - Monk-Steel, A.D.; Thompson, D.J.; de Beer, F.G.; Janssens, M.H.A. (Journal of sound and vibration, 2006)
Curve squeal noise is of growing concern for the railway industry as rail systems become more widespread in densely populated areas. In response to the pressure to minimise environmental pollution, there is a demand for a deeper understanding of the phenomenon and to develop a methodical approach to managing the wheel–rail system. Under curving, the wheel and the rail are subject to creep forces due to relative motion (creepage) within the contact region. In tight curves, these creep forces can cause unstable vibration of the wheel, leading to the radiation of squeal noise. The occurrence and characteristics of this are governed by the configuration of the creepages at the wheel–rail contact, which can have longitudinal, lateral and spin components. It follows that the representation of creepage is important in modelling the mechanisms of squeal noise behaviour. An investigation is presented into how the relationship between lateral creepage and creep force is affected when a component of longitudinal creepage is introduced. A 1:3 scale laboratory test rig has been modified to simulate contact conditions with controlled levels of lateral and longitudinal creepage, and to measure the salient system parameters. The experimental results are presented and discussed here.